Hegemonic Globalisation : U.S. Centrality and Global Strategy in the Emerging World Order. - Duong, Thanh (Taylor and Francis, 2017)
"This title was first published in 2002. This innovative work analyses how the United States has laid down the foundations for global power. It reassesses and re-evaluates the declinist-renewal argument and challenges conventional balance of power theories, demonstrating how the United States is attempting to 'hegemonically globalise' the entire international system. To evaluate the success of hegemonic globalisation, the book analyses four major powers and regions - Russia, the People's Republic of China (PRC), the European Union (EU), and Japan - and their historical, political, economic, cultural and geopolitical relations with the United States. Each study examines the tangible and intangible sources of their relationship, and the possible tensions and resistance towards United States hegemony therein. Providing much-needed insight and a fresh perspective, this book makes a worthwhile contribution to our understanding of contemporary international power."--Provided by publisher.